Optimizing lucerne (Medicago sativa) termination on the Loess Plateau, China: a comparative analysis of conventional tillage and herbicide treatments - Zhao, Yixuan; Guo, Junhong; Luo, Shiheng; Shen, Yuying; Siddique, Kadambot H. M.; Li, Yuan (Frontiers in Sustainable Food Systems, 2023)
Introduction Lucerne (Medicago sativa L.) is a crucial component in agricultural rotation systems due to its ability to enhance soil carbon (C) and nitrogen (N) contents. In China, conventional tillage (CT) is commonly used for lucerne termination, leading to soil structure degradation and C and N losses. While herbicide application has been suggested for lucerne termination in the United States and EU, its impact on lucerne growth suppression and soil C and N contents in China remains uncertain. Methods In this study, we examined the effects of herbicide type [glyphosate and 2,4-D (G + 2), glyphosate and dicamba (G + D), 2,4-D and dicamba (2 + D), with water (W) and CT as controls] and concentration (100, 200, 300%) on various lucerne and soil properties. Results and Discussion Our findings revealed that G + 2 and 2 + D treatments significantly reduced the regreening rate, and the recommended herbicide concentration (100%) was sufficient for lucerne termination. CT and W treatments resulted in a higher soil pH compared to herbicide treatments. Moreover, herbicide treatments exhibited higher soil organic C (SOC) and total N (TN) levels than the CT treatment. The 2 + D treatment demonstrated a higher SOC content compared to the G + 2 treatment, while the 200 and 300% herbicide concentrations reduced SOC and TN levels. The G + 2 treatment had the highest soil ammonium nitrogen content (7.94 ± 1.45 mg kg−1), while the CT treatment showed the lowest (6.46 ± 1.54 mg kg−1). In conclusion, our study suggests that applying the recommended herbicide dosage (100%) effectively terminates lucerne grassland on the Loess Plateau of China without negatively impacting soil C and N storage. Finally, it is important to acknowledge that one-year trials at a single site have inherent limitations, and the findings should be considered cautiously when informing policy decisions.